Effects Of Washing With Potassium And Sodium Hydroxide Mixtures In The Development Of Rancidity In Black Tilapia (Oreochromis Mossambicus) Fillets And The Frying Oil - Yusoff, Anida (2003)
A study was carried out to determine the effectiveness of potassium hydroxide (KOH) and sodium hydroxide (NaOH) in removing the earthy flavor and odor in black tilapia (Oreochromis mossambicus) muscle. Four different mixtures of KOH and NaOH were also prepared, each in three different ratios. The range of concentration used were O.OS - 0.S4N for individual KOH and NaOH washing solutions and between 0.OS4N to 0.216N for the mix solution. Their effects on frying of treated breaded fillets on the rancidity development and physico-chemical changes in refined bleached and deodorized (RBD) palm olein, the frying oil used was also carried out. Washing treatment with either KOH or NaOH solution was found to affect the rancidity development of the muscle. PV and TBARS values were significantly increased (p<O.OS) in all treatments. The absorbance for hydroperoxides at 174S cm,l using Fourier Transform Infrared (FTIR) spectroscopy for oil extracted from all treated fillets also increased. The correlation coefficients (R2) between absorbance versus PV for KOH and NaOH were 0.8467 and 0.6651, respectively. Fatty acids composition and fatty acids ratios (CI8·I+CI8.2)/CI6:0 and C18.2/C16 0 showed a decreasing trend in total unsaturated fatty acids with increasing concentration of washing solutions. Nineteen triglycerides were determined and only four were detected in the samples.